Psychological morbidity and health related quality of life after injury: multicentre cohort study - Kendrick, Denise; Kellezi, Blerina; Coupland, Carol; Maula, A.; Beckett, Kate; Morriss, Richard K.; Joseph, Stephen; Barnes, Jo; Sleney, Jude; Christie, Nicola (Springer, 2017)
Purpose: To demonstrate the impact of psychological morbidity one month post-injury on subsequent post-injury quality of life (HRQoL) in a general injury population in the UK to inform development of trauma care and rehabilitation services.